Adequate exercise response at artificial altitude in Fontan patients - Müller, Nicole; Herberg, Ulrike; Jung, Thomas; Breuer, Johannes; Härtel, Julian Alexander (Frontiers in Pediatrics, 2022)
Purpose: For Fontan palliated patients altitude exposure is still part of discussion, since the extent of hypoxic pulmonary vasoconstriction potentially resulting in decreasing cardiac output (Qc), especially during physical exercise, is still unclear. We investigated the effects of normobaric hypoxia (15.2% O2) simulating 2,500 meters above sea level on cardiopulmonary and metabolic parameters and the benefit of daily physical activity (PA) on hypoxic exercise capacity. Methods: 21 Fontan patients (14-31 years) and 20 healthy controls performed cardiopulmonary exercise tests on a bicycle ergometer in normoxia and hypoxia until subjective exhaustion, measuring capillary lactate (cLa) every 2 minutes. In between, participants underwent an activity tracking over 5 days with a triaxial accelerometer. Results: Hypoxic exercise was well tolerated by Fontan patients and no adverse clinical events were observed. Fontan patients showed reduced physical capacity under both conditions compared to controls (63% normoxia, 62 % hypoxia), but the relative impairment due to hypoxia was similar for both (≈ 10%). Up to workloads of 2 W/kg oxygen uptake (V ̇O2) and heart rate (HR) developed similar in patients and controls. cLa increased faster in relation to workload in Fontan patients, but remained significantly lower at peak workload (normoxia 3.88 ± 1.19 vs. 7.05 ± 2.1; hypoxia 4.01 ± 1.12 vs. 7.56 ± 1.82). Qc was diminished but could be increased similar to controls. Fontan patients with higher PA-levels showed a higher V ̇O2peak in hypoxia. Conclusion: Exercise during short time artificial altitude exposure seems to be safe for young Fontan patients. Further studies are needed to validate longer exposure under real condition. V ̇O2, HR and Qc might not be a limiting factor for exercise until workloads of 2 W/kg. Higher daily PA-levels might improve physical capacity under altitude conditions.